2016
DOI: 10.1016/j.matbio.2015.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Sclerostin antibody (Scl-Ab) improves osteomalacia phenotype in dentin matrix protein 1(Dmp1) knockout mice with little impact on serum levels of phosphorus and FGF23

Abstract: Unlike treatments for most rickets, the treatment using 1,25-(OH)2 vitamin D3 has little efficacy on patients with hypophosphatemic rickets, a set of rare genetic diseases. Thus, understanding the local cause for osteomalacia in hypophosphatemic rickets and developing an effective treatment to restore mineralization in this rare disease has been a longstanding goal in medicine. Here, we used Dmp1 knockout (KO) mice (whose mutations led to the same type of autosomal recessive hypophosphatemic rickets in humans)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 44 publications
3
19
2
Order By: Relevance
“…(13) Scl-Ab treatment increases bone mass and, subsequently, bone strength in several preclinical animal models, including postmenopausal osteoporosis, (34) osteogenesis imperfecta, (16,35) and autosomal recessive hypophosphatemic rickets. (17) Consistent with this, we find that Scl-Ab induces gains in bone mass in Hyp animals with the largest gains in the cortical compartment. Previous studies have demonstrated that Scl-Ab activates bone lining cells on existing bone surfaces and sustains osteoprogenitor cell recruitment to increase bone mass.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…(13) Scl-Ab treatment increases bone mass and, subsequently, bone strength in several preclinical animal models, including postmenopausal osteoporosis, (34) osteogenesis imperfecta, (16,35) and autosomal recessive hypophosphatemic rickets. (17) Consistent with this, we find that Scl-Ab induces gains in bone mass in Hyp animals with the largest gains in the cortical compartment. Previous studies have demonstrated that Scl-Ab activates bone lining cells on existing bone surfaces and sustains osteoprogenitor cell recruitment to increase bone mass.…”
Section: Discussionsupporting
confidence: 88%
“…The Scl-Ab dosing strategy was chosen based on previous publications testing the efficacy of Scl-Ab in preclinical rodent models. (7,(15)(16)(17) Treatment was initiated at weaning (4 weeks of age) and continued for 4 weeks until euthanization at 8 weeks of age. All animal studies were approved by the Rush University Institutional Animal Care and Use Committee.…”
Section: Animalsmentioning
confidence: 99%
“…This is a mouse model of hypophosphatemic rickets manifested by osteomalacia in the setting of low serum phosphorus levels and elevated FGF-23 levels. (82) Interestingly, Sclerostin antibody treatment for 8 weeks in both 1 month and 3-month-old animals significantly improved (but did not completely restore) alveolar bone morphology and volume. (82) Sclerostin antibody also increased long bone volume and strength suggesting there may be a role for Sclerostin inhibition in the treatment of hypophosphatemic rickets.…”
Section: Other Disorders Of Bone Densitymentioning
confidence: 95%
“…(82) Interestingly, Sclerostin antibody treatment for 8 weeks in both 1 month and 3-month-old animals significantly improved (but did not completely restore) alveolar bone morphology and volume. (82) Sclerostin antibody also increased long bone volume and strength suggesting there may be a role for Sclerostin inhibition in the treatment of hypophosphatemic rickets. (82) Together these studies suggest a role for systemic Sclerostin antibody therapy in the treatment of alveolar bone loss due to periodontitis and hypophosphatemic rickets induced osteomalacia.…”
Section: Other Disorders Of Bone Densitymentioning
confidence: 99%
See 1 more Smart Citation